2020
DOI: 10.2147/ott.s219959
|View full text |Cite
|
Sign up to set email alerts
|

<p>Targeting the MET-Signaling Pathway in Non-Small–Cell Lung Cancer: Evidence to Date</p>

Abstract: The c-MET proto-oncogene (MET) plays an important role in lung oncogenesis, affecting cancer-cell survival, growth and invasiveness. The MET receptor in non-small-cell lung cancer (NSCLC) is a potential therapeutic target. The development of high-output nextgeneration sequencing techniques has enabled better identification of anomalies in the MET pathway, like the MET exon-14 (METex14) mutation. Moreover, analyses of epidermal growth factor-receptor (EGFR) and mechanisms of resistance to tyrosine-kinase inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…More recently, the updated data reported an overall response rate (ORR) of 32% and a median progression-free survival (mPFS) of 7.3 months [21]. Many Phase I-II (e.g., AcSè, METROS) and retrospective analyses confirmed the reported activity and survival results [16,[22][23][24]. In these studies, crizotinib reported similar results in MET-amplified patients.…”
Section: Crizotinibmentioning
confidence: 86%
See 3 more Smart Citations
“…More recently, the updated data reported an overall response rate (ORR) of 32% and a median progression-free survival (mPFS) of 7.3 months [21]. Many Phase I-II (e.g., AcSè, METROS) and retrospective analyses confirmed the reported activity and survival results [16,[22][23][24]. In these studies, crizotinib reported similar results in MET-amplified patients.…”
Section: Crizotinibmentioning
confidence: 86%
“…The binding of MET to its ligand HGF leads to its homodimerization with subsequent auto-phosphorylation and activation of the intracellular tyrosine kinase domains. The activation of c-MET stimulates many downstream signaling pathways, including mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK), phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT), mammalian target of rapamycin (mTOR), and Janus kinase (JAK)/signal transducer and activator of transcription (STAT) pathways [ 9 , 16 ]. These pathways are involved in cell survival, proliferation, migration, invasion, angiogenesis, and the epithelial-to-mesenchymal transition.…”
Section: Metmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5,7,8 Hepatocyte growth factor receptor, or c-mesenchymalepithelial transition factor (c-met) is a cell surface protein tyrosine kinase. [9][10][11][12] It plays important roles not only in embryogenesis, organ development and differentiation but also in tumor cell migration, proliferation, and invasion in a variety of cancers including breast cancer, lung cancer, and renal cancer. [9][10][11][13][14][15][16][17] Based on these findings, drugs that target c-met, such as TKIs and antibody-drug conjugates, are currently under development, and crizotinib has been approved for non-small-cell lung cancer in some countries.…”
mentioning
confidence: 99%